The efficiency and inefficiency of the banking sectors: evidence from selected ASEAN banking - Abdul Mongid; Muazaroh Muazaroh (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper examines the cost efficiency of banks operating in selected countries of the Association of Southeast Asian Nations (ASEAN). We calculate the cost efficiency base on accounting efficiency and economic efficiency using Stochastic Frontier Analysis (SFA) and then classify it as efficient and not. Further, bank specific and economic variables are combined to determine the cost efficiency and the efficiency category (efficiency dummy) using linear regression and logistic regression. The results show that bank efficiency determined by asset size, dummy of economic crisis, interest rate gap, economic growth, inflation, capital, earning assets and loan losses provision. Only capital, earning asset and loan loss provision are consistent for accounting and economic efficiencies. For economic variable, economic growth and inflation rate are only significant in the accounting efficiency. The result implied that ASEAN banking should continue to consolidate the asset size and the authority should create high economic growth and a low inflation environment to make their banking industry more efficient.